A economia do desenvolvimento em perspectiva histórica: novos rumos da disciplina - Bonente, Bianca Aires Imbiriba Di Maio (2007)
In the post-War period rises in Economics something known as Economic Development. However, if it is true that the Development Economics had achieved an incredible success, it is also true that it had a real short lifetime. As result of that process, the development thematic became vague, especially due to the incorporation of new themes within it. To the substantive "development" new adjectives were attached, giving to the term a pretense multiplicity. This fragmentation of the discipline originated a series of subthematics that made the development studies more complex and difficult to be understood in its global dimension. Looking more carefully at these questions, this paper seeks by rescuing the old Development Economics and the major historical changes in the world's scenario to explain (1) new paths in this discipline, (2) processes that lead to the historical changes of the development economics debate into a fragmented one, and (3) the nature of this fragmentation. Due the natural limitations of this work and the large number of theories in economic development field, the local and territorial development theories has been chosen as representative of the New Development Economics.